2006
DOI: 10.1097/01.ta.0000229960.31334.ca
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Isolated Celiac Axis Injury by Blunt Abdominal Trauma

Abstract: A lthough blunt abdominal trauma is common, injury to the celiac axis (CA) is a rare occurrence, but with significant mortality. This report describes and discusses the presentation and management of one patient with an isolated CA injury in context with the literature. CASE REPORTA 39-year-old, previously healthy, man with no history of trauma was transferred from a referring institution after suffering direct compression from the tailgate of a cargo truck. On presentation to the emergency department, the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…Isolated CA injury, which is an injury to the CA without concomitant aortic injury, is the least common among all abdominal arterial injuries. To date, only 8 reports of isolated CA injury following blunt trauma have been reported [2][3][4][5][6][7][8][9]. These cases, except for 1 case without a detailed description, are summarized, along with our two cases, in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated CA injury, which is an injury to the CA without concomitant aortic injury, is the least common among all abdominal arterial injuries. To date, only 8 reports of isolated CA injury following blunt trauma have been reported [2][3][4][5][6][7][8][9]. These cases, except for 1 case without a detailed description, are summarized, along with our two cases, in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…These cases, except for 1 case without a detailed description, are summarized, along with our two cases, in Table 1. All but one of the injuries (CA rupture managed by surgical ligation) [3], including our two cases, were CA dissections. In this report, we focus on the clinical presentation, treatment, and outcomes of these isolated CA dissections.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of cases, traumatic injury to the coeliac artery is associated with injury to other intra-abdominal organs, including the small bowel, duodenum, pancreas, colon or stomach. Only a few cases of isolated blunt traumatic injury to the coeliac axis have been reported [2][3][4][5]. The intimate anatomical relationship of the coeliac axis to the median arcuate ligament has been proposed as a factor contributing to isolated coeliac artery injury secondary to blunt trauma.…”
Section: Discussionmentioning
confidence: 99%
“…12 This intimate anatomic relationship, coupled with rapid deceleration and an anteroposterior crush, has been proposed as a possible mechanism of isolated injury to the CA in blunt trauma. 11,13 A fall from 900 cm, as occurred with our The management of CA injury has varied. Active hemorrhage from the CA is an emergency requiring prompt laparotomy with or without left thoracotomy to expose the root of the vessel and allow for its repair or ligation.…”
Section: Commentmentioning
confidence: 94%
“…9-11 Linuma et al 11 described a tear in the CA diagnosed on initial CT that demonstrated extravasation of contrast media around the vessel's origin. The patient underwent left thoracotomy and upper laparotomy to ligate the CA at its base.…”
Section: Commentmentioning
confidence: 98%